SAT0294 Circulating LIN1-DABP-CD34+CD133+CD309+ Endothelial Progenitor Cells (EPC) Are Reduced in Patients with Systemic Lupus Erythematosus (SLE) but Not Associated with Biophysical Markers of Cardiovascular Disease (CVD). (15th July 2016) - Mak, A.; Ling, L.; Kow, N.; Fairhurst, A.M.
Abstract : Background: Dysfunctional EPC have been proposed to contribute to CVD in SLE patients. Due to various methodological flaws in identifying the rare EPC population in previous studies, how the true circulating EPC count is altered in SLE patients remains unclear. Furthermore, how the EPC population correlates with the biophysical markers of CVD in SLE patients has not been adequately addressed. Objectives: To quantify and compare circulating EPC count between SLE patients and healthy controls (HC) based on a stringently modified EPC identification method proposed by the European League Against Rheumatism Scleroderma Trials and Research (EUSTAR) group that involves lineage-positive and dead-cell exclusion and fluorosphere calibration (1). To address the functional relevance of EPC by evaluating the relationship between EPC count and biophysical markers of CVD in SLE patients. Methods: Peripheral blood (32ml) were obtained from SLE patients and HC naïve of CVD, cerebrovascular disease, diabetes mellitus and antiphospholipid syndrome. Clinical and serological parameters of SLE patients were collected. The peripheral blood mononuclear cell (PBMC) fraction was prepared for flow cytometry. Singlets were gated from the PBMC population, followed by exclusion of the lineage-positive (Lin-1 FITC+) and dead cells (DAPI+). To mitigate the issue of autofluoresence, 3 fluorescence-minus-one (FMO) panels (panels stained all but one respective fluorochrome) were designed. From the Lin1-DAPI- population, CD309-APC, CD133-PE and CD34-PerCP-Cy5.5 were gated from the corresponding FMO panels. All the FMO gates were then applied on the all-stained samples to identify the true EPC population (Lin1-DAPI-CD34+CD133+CD309+). The absolute EPC counts were calculated by fluorosphere calibration. Endothelial reactivity, arterial stiffness and carotid atherosclerosis were assessed by brachial artery flow-mediated dilation (FMD), pulse-wave velocity (PWV) and carotid intima-media thickness (cIMT) respectively. Relationships between EPC count and disease-related factors, FMD, PWV and cIMT were studied by Spearman correlations. Results: Thirty SLE patients and 22 HC (5 and 3 men in SLE and HC groups respectively, p=1.0) were studied. Mean±SD age of SLE patients and HC was 34.63±11.5 and 31.87±8.4 years respectively (p=0.34). The mean±SD disease duration, daily prednisolone dose, atherogenic index (AI) (total cholesterol/HDLc), SLEDAI and SLICC/DI were 60.17± 69.4 months, 14.77±16.5 mg, 3.49±0.9, 5.53± 5.4 and 0.10±0.3 respectively in SLE patients. Mean±SD EPC count in SLE patients was significantly lower than that of HC (3.93±4.4 vs. 9.24±8.5 cells/ml, p=0.014), despite ANCOVA adjustment for PBMC count (p=0.018). No significant relationships were found between EPC count and disease duration, daily prednisolone dose, AI, SLEDAI, SLICC/DI, FMD, PWV and cIMT in SLE patients. Conclusions: Incorporating the FMO gating strategy into the EUSTAR recommendation of EPC identification confirmed significantly lower circulating EPC count in SLE patients as compared to HC, but the reduced EPC level was not associated with biophysical CVD markers in SLE patients. Prospective studies are needed to address the impact of reduced EPC on CVD in SLE patients. References: Kuwana M et al. Ann Rheum Dis 2012;71:617–20 Disclosure of Interest: None declared